1995
DOI: 10.1002/jlac.1995199509231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical properties of 4‐phenyl‐1‐buten‐3‐yne‐1,1,2‐tricarbonitriles and tricyanoacrylates

Abstract: The reaction of phenylacetylenes 4a-h with copper(1) acetate (5) and TCNE (tetracyanoethylene) in THFIacetonitrile gave 4-phenyl-l-buten-3-yne-l,1,2-tricarbonitriles 6a-h. 4i did not react to give 6i. The phenylacetylenes 4b-i were prepared by a two-step synthesis starting from the corresponding phenyl halides lb-i. The tricyanoacrylates 8 were synthesized from the corresponding cyanoacetates ?, TCNE and catalytic amounts of pyridine in THE -Cyclovoltammetric investigations showed that the butenynes 6 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Synthesis of donor-substituted CEEs: In contrast to the high reactivity of CEE 8, the DMA donor-substituted tricyanoethynylethene 19, prepared according to Dulog et al [11] by reacting TNCE with the copper(i) acetylide formed from N,N-dimethyl-4-ethynylaniline (Scheme 1), features high stability. Solutions of 19 are bright blue, and the shiny metallic solid can be sublimed undecomposed at 100 8C/0.1 mbar.…”
Section: Synthesis Of Dimeric Cyanoethynylethenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of donor-substituted CEEs: In contrast to the high reactivity of CEE 8, the DMA donor-substituted tricyanoethynylethene 19, prepared according to Dulog et al [11] by reacting TNCE with the copper(i) acetylide formed from N,N-dimethyl-4-ethynylaniline (Scheme 1), features high stability. Solutions of 19 are bright blue, and the shiny metallic solid can be sublimed undecomposed at 100 8C/0.1 mbar.…”
Section: Synthesis Of Dimeric Cyanoethynylethenesmentioning
confidence: 99%
“…Dulog et al reported the synthesis of several aryl-substituted tricyanomonoethynylethenes [11] from TCNE and copper(i) arylacetylides, prepared from the corresponding acetylenes with CuOAc. The yield of this nucleophilic additionelimination reaction increased with increasing electron-donating character of the aryl ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first class of potent electron acceptors, which we developed, are the cyanoethynylethenes (CEEs), of which only two derivatives had been reported previously [71,72]. CEEs are hybrid derivatives combining the synthetic versatility of TEEs for the construction of π-conjugated scaffolds with the [73]; all potentials in this review are measured under these conditions using cyclic voltammetry (CV) or rotating disc voltammetry (RDV)] (Fig.…”
Section: Cyanoethynylethenes: Property Tuning In Charge-transfer Chromentioning
confidence: 99%
“…However, it does not contain vectors for functionalization and incorporation into larger molecular frameworks. This led us to develop a class of TEE-TCNE hybrids, the CEEs of which only two derivatives had been previously reported [46,47].…”
Section: Cyanoethynylethenes: a New Class Of Powerful Electron Acceptorsmentioning
confidence: 99%